The structural analysis and its hepatoprotective activity of melanin isolated from Lachnum sp. (March 2020) - Xu, Can; Chen, Tingting; Li, Jinglei; Jin, Mingzhi; Ye, Ming
Graphical abstract: Highlights: The possible structural formula of the intracellular homogeneous melanin of Lachnum YM30 (LIM) was concluded. LIM could protect the liver and combined treatment group could further reduce the inflammatory effect of the model drug on the mice compared with the single positive drug treatment or the melanin treatment groups. In this study, we formulated the structural information of LIM from Lachnum YM30 and the mechanism of its protective effect on liver injury, analyzing the relationship between its structure and anti-oxidation, anti-inflammation for the first time, compared to previous studies. LIM are potential prophylactic agents that can be used to prevent LPS/GalN-induced liver injury and that combination therapy is also a potential treatment for reducing liver injury in the model. Abstract: In the present study, an intracellular melanin (LIM) isolated from Lachnum YM30 was obtained by submerged fermentation, extraction and purification. The possible structural formula of LIM was concluded, based on Ultraviolet (UV) analysis, IR analysis, elemental analysis, Nuclear Magnetic Resonance (NMR) and ESI-MS analysis, which showed the typical feature of fungal eumelanin. The hepatoprotective effect of LIM was evaluated in an acute LPS/D-GalN induced liver injury mouse model that was proved by the declining of alanine aminotransferase (ALT) and aspartate transaminase (AST), enhancing the content of anti-inflammatory factors interleukin-4 (IL-4) and interleukin-10 (IL-10). Concurrently, LIM could alleviate LPS/D-GalN toxicity through the effects of NF-kappa B (NF-κB) signaling pathway and its related cytokines interleukin-1β (IL-1β), tumor necrosis factor alpha (TNF-α) and interleukin-8 (IL-8). The mechanisms underlying the protective effect might be related to inhibition of nuclear factor-kappa B activation and the functional groups of LIM. And compared with the single positive drug treatment or the melanin, the results showed that the combined treatment group could further reduce the inflammatory reaction of the model mice.